Proof of long-term immunological memory in cartilaginous fishes. (July 2020) - Eve, Oliver; Matz, Hanover; Dooley, Helen
Abstract: Immunological memory provides long-term protection against pathogen re-infection and is the foundation for successful vaccination. We have previously shown an antigen-specific recall response in nurse sharks almost one year after primary exposure. Herein, we extend the time between prime and successful recall to >8 years, the longest period for which immunological memory has been shown in any non-mammalian vertebrate. We confirm that antigen binding is mediated by monomeric IgM and IgNAR, but not pentameric IgM, in both the primary and recall phases. Our inability to find target-binding clones in recombinant VNAR expression libraries suggests that, at least in this instance, antigen-specific memory cells comprise a small fraction of the IgNAR-positive B cells in epigonal and spleen. Further, that the few memory cells present can generate a robust antigen-specific IgNAR titer following re-stimulation. Our results continue to challenge the long-held, but erroneous, belief that the shark adaptive immune system is 'primitive' when compared to that of mammals. Highlights: A primary antibody response was raised in a nurse shark via immunization. The shark was rested for 8 years without further exposure to the antigen. Re-stimulation with soluble antigen induced a robust and specific antibody recall response. Antigen binding is mediated by monomeric IgM and IgNAR, not pentameric IgM, in the recall phase. This is the longest memory period recorded for any non-mammalian vertebrate to date.